All Fun and Cool Clothes? Youth Workers' Consumer Identity in Clothing Retail. (August 2016) - Misra, Joya; Walters, Kyla
Retail offers notoriously bad jobs that exist at the nexus of work and consumption. Previous brand-based retail studies assert that youth workers see the stores' coolness and the employee discount as compensating for the low pay and variable schedules. The authors use interviews with 55 former and current young clothing retail workers to examine how they experience retail work in relation to their consumer identities. The authors find that while some workers identify with the brand, all workers criticize the poor working conditions. Workers draw on their consumer identities to understand what good service entails and sometimes to resist managers' orders that they interpret as bad deals for shoppers. This article concludes that youth retail workers' consumer identities do not compensate for the low pay and poor work conditions but instead help them navigate the interactive aspects of service work and find fulfillment on the job.